Penerapan Fungsi Actuating dalam Manajemen Bisnis Islam pada Kedai Kopi 3 Sisi - Rizki Ardiansyah; Moh Jayyid Abadi; Allifna An Nauroh; Habibah Habibah; Mei Nurus Syamsiyah Yulianti; Abd Halim; Choirul Anam; Siti Zubaidah (Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the implementation of the actuating function in Islamic business management at Kedai Kopi 3 Sisi. The actuating function, which includes leadership, communication, directing, and motivation, is crucial in mobilizing human resources to work effectively and align with organizational goals. This research employs a descriptive qualitative approach, with data collected through participatory observation, in-depth interviews, and documentation. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, comprising data reduction, data presentation, and conclusion verification. The results indicate that Kedai Kopi 3 Sisi consistently applies Islamic business management through financial transparency, adherence to halal products, and integration of religious values in operational practices. The actuating function is implemented through leadership that is both firm and participative, open communication, systematic directing, and motivation that balances material and spiritual incentives. This implementation not only improves service quality and customer satisfaction but also strengthens Islamic values within the SME work culture. This study contributes theoretically to the literature on Islamic business management and provides practical benefits for SMEs in enhancing competitiveness based on sharia principles. Penelitian ini bertujuan untuk menganalisis penerapan fungsi actuating dalam manajemen bisnis Islam pada Kedai Kopi 3 Sisi. Fungsi actuating, yang mencakup kepemimpinan, komunikasi, pengarahan, dan motivasi, merupakan kunci untuk menggerakkan sumber daya manusia agar bekerja secara efektif dan selaras dengan tujuan organisasi. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi partisipatif, wawancara mendalam, dan dokumentasi. Analisis data dilakukan menggunakan model interaktif Miles, Huberman, dan Saldaña yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan/verifikasi. Hasil penelitian menunjukkan bahwa Kedai Kopi 3 Sisi menerapkan manajemen bisnis Islam secara konsisten melalui transparansi keuangan, kepatuhan terhadap kehalalan produk, dan integrasi nilai religius dalam praktik operasional. Fungsi actuating dijalankan melalui kepemimpinan yang tegas namun partisipatif, komunikasi terbuka, pengarahan yang sistematis, serta motivasi yang seimbang antara insentif material dan spiritual. Implementasi ini tidak hanya meningkatkan kualitas layanan dan kepuasan konsumen, tetapi juga memperkuat nilai-nilai Islam dalam budaya kerja UMKM. Penelitian ini memberikan kontribusi teoretis bagi literatur manajemen bisnis Islam serta manfaat praktis bagi pelaku UMKM dalam meningkatkan daya saing berbasis nilai syariah.